Super-hydrophobic polyurethane sponges for oil absorption. Issue 2 (22nd January 2017) - Wang, Zhe; Ma, Hongyang; Chu, Benjamin; Hsiao, Benjamin S.
ABSTRACT: Porous polyurethane (PU) sponge was modified with polyhedral oligmeric silsesquioxane (POSS), where the resulting material exhibited super-hydrophobic property with very high oil absorption capability. The structure and morphology of PU sponges before and after the POSS modification were characterized. Varying motor oils with different viscosity, surface tension, and density were also chosen to test the oil–water separation efficiency, where the effects of oil viscosity and PU sponge pore size on the absorption capacity were correlated. Based on the excellent mechanical properties, POSS-modified PU sponges could be recycled and reused for many times without losing the absorption capacity for motor oil.